2016
DOI: 10.1289/ehp.1409501
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arsenite Exposure during Fetal Development on Energy Metabolism and Susceptibility to Diet-Induced Fatty Liver Disease in Male Mice

Abstract: BackgroundChronic exposure to arsenicals at various life stages and across a range of exposures has been implicated in cardiometabolic and liver disease, but disease predisposition from developmental exposures remains unclear.ObjectivesIn utero and post-weaning exposure to trivalent arsenic (AsIII) was examined on the background of a Western-style diet to determine whether AsIII exposure affects metabolic disease.MethodsMale Swiss Webster mice were exposed to 100 ppb AsIII in utero, after weaning, or both. Ad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 48 publications
2
62
0
Order By: Relevance
“…Interestingly, the same has been reported for low levels of some mitotoxicants, such as arsenic (Schmeisser et al 2013); however, we recently found that concentrations of arsenic that were harmless or even beneficial in wild-type Caenorhabditis elegans were instead toxic to fusion-deficient individuals (Luz et al 2017). On the other hand, some mitochondrial perturbations can have persistent, deleterious consequences (Berthiaume and Wallace 2007a, b; Chan et al 2007; Ditzel et al 2015; Divi et al 2010; Leung et al 2013; Saben et al 2016; Wood et al 2015), and thus may contribute the developmental origins of adult health and disease. Testing this possibility will be an additional, important future direction, especially given the very different mitochondrial morphologies and functions observed in early-stage organisms and undifferentiated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the same has been reported for low levels of some mitotoxicants, such as arsenic (Schmeisser et al 2013); however, we recently found that concentrations of arsenic that were harmless or even beneficial in wild-type Caenorhabditis elegans were instead toxic to fusion-deficient individuals (Luz et al 2017). On the other hand, some mitochondrial perturbations can have persistent, deleterious consequences (Berthiaume and Wallace 2007a, b; Chan et al 2007; Ditzel et al 2015; Divi et al 2010; Leung et al 2013; Saben et al 2016; Wood et al 2015), and thus may contribute the developmental origins of adult health and disease. Testing this possibility will be an additional, important future direction, especially given the very different mitochondrial morphologies and functions observed in early-stage organisms and undifferentiated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Of the toxicants tested, arsenite may have the highest potential for human health relevance, as over 140 million people worldwide are chronically exposed to arsenite via consumption of contaminated drinking water (Chowdhury et al 2006; Ravenscroft et al 2009). Although chronic arsenite exposure is associated with cancer (Gilbert-Diamond et al 2013; Karagas et al 2004; Marshall et al 2007; Yu et al 2006), and other metabolism-related pathologies (Ditzel et al 2015; Sanchez-Soria et al 2014; Shi et al 2013), the precise mechanisms underlying pathogenesis are complex, and remain poorly understood. We also demonstrate that arsenite disrupts mitochondrial energy metabolism in fusion ( fzo-1 , eat-3 )-deficient nematodes, while increasing mitochondrial function in wild-type nematodes, and has minimal effect on mitochondrial function in fission ( drp-1 )-deficient nematodes.…”
Section: Introductionmentioning
confidence: 99%
“…Male mice exposed to 100 ppb As (III) after weaning while on a Western diet do not develop NASH . Increased TAG accumulation was not detected in adult primary hepatocytes from combination exposure to Intralipid and As (III) compared with intralipid exposure alone (Supplementary Figure S1B).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have linked exposures to arsenite at part per million [ppm) concentrations to the development of NAFLD [3−6]; however, these exposure scenarios are not necessarily representative of more frequent levels of arsenite present in water [7]. Our laboratory recently demonstrated that exposure to 100 part per billion (ppb) arsenite during development, in conjunction with a Western style diet, results in significantly worsened NAFLD and NASH in male Swiss Webster mice [8].…”
Section: Introductionmentioning
confidence: 99%